Efektivitas Efektivitas Model Pembelajaran Project Based Learning Terhadap Soft Skill Berfikir Kritis dan Kreatif Peserta Didik: Meta Analisis - Sri Zulfia Novrita; Ambiyar, Ambiyar; Syah, Nurhasan (Jurnal Pendidikan Tambusai, 2024)
Facing the complexity of life's challenges In this 21st century, students must be prepared with high-level soft skills so they can compete effectively in the dynamics of this era of globalization. The purpose of this research is to show the Project Based Learning (PjBL) learning model affects students' soft skills in critical and creative thinking. In order to identify the Project Based Learning learning model, a review of relevant literature is conducted as part of the meta analysis research method. After reviewing the literature, research characteristics and determined article analysis criteria, a sample of 25 articles was obtained that met the requirements for this meta-research. The effectiveness of the Project Based Learning learning model for junior high school students shows a medium effect size (0,68), while the high category is tained for elementary school students (2,41), SMA/SMK (1.79) and tertiary institutions (1,30). The effectiveness of the Project Base Learning learning model based on soft skills achieved resulted in a high category effect size for achieving critical thinking (1,33), creative (1,69) learning motivation (1,33). This is a fairly large impact according to Cohen's criteria and shows that the Project Based Learning learning model is more effective in education in improving critical and creative thinking soft skills and can increase students' learning motivation.